Registro de ataque de perros domésticos (Canis lupus familiaris) a zambullidores del Titicaca (Rollandia microptera) en una zona periurbana lacustre en Puno, Perú - Elías Piperis, Roberto K. (2024)
In the shore zone of Lake Titicaca, some of the resident wild species come to cohabit rural and urban spaces, where they interact with domestic animals. The aim of this report is to document the first videographic record of the attack by domestic dogs on Titicaca grebe (Rollandia microptera) in a water channel from the Suchipujio spring on the shores of Lake Titicaca, Yunguyo district, Puno, Peru. The images were obtained with a mobile device and the videographic product (which consists of two videos) was deposited in the specialized digital collection of the National Autonomous University of Mexico. The videos show the attack (chasing, barking and biting) of dogs on these threatened birds.